HUBUNGAN KESEGARAN JASMANI TERHADAP HASIL BELAJAR MATA PELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN (PENJASORKES) SISWA SDN 28 SENGGORO KECAMATAN BENGKALIS KABUPATEN BENGKALIS - Dimasri, Dimasri; Slamet, Slamet; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT, Based on observations made in the field of the students of SDN 28 Senggoro District of Bengkalis that follow subjects in the orchestra found the lack of achievement of physical education on learning outcomes of students in these subjects. The purpose of this study was to investigate the relationship between physical fitness with the learning outcomes of students of SDN 28 Senggoro penjasorkes Bengkalis District of Bengkalis. This study is correlational is to determine how far a variable related to other variables. The population in this study were all students of SDN 28 Senggoro Bengkalis District of Bengkalis. Sampling was done by using purposive sampling that students of class V only .. Data were analyzed by Product Moment formula using Lilliefors test. The result showed that the correlation coefficient of 25 male students of SDN 28 Senggoro Bengkalis District of Bengkalis shows that there is a significant relationship between physical fitness on learning outcomes, which rhitung (0.45)> rtabel (.396) with a contribution of 20% , Then the results obtained from 16 female students of SDN 28 Senggoro Bengkalis District of Bengkalis shows that there is a significant relationship between physical fitness on learning outcomes, which rhitung (0.87)> rtabel (.497) with a contribution of 76%. In connection with this finding suggested some efforts on the teacher to pay attention to the physical fitness of students in order to get a good penjasorkes learning outcomes.Keywords : Physical Fitnees, Learning Outcomes